The vernacularization of non-native items in early english medical writing - Romero-Barranco, Jesús (My University, 2017)
Early Modern English is characterised by an extraordinary lexical growth motivated by two main linguistic processes, borrowing and word-formation (Nevalainen 1999: 332). Within affixation, prefixation grew more than suffixation in early Modern English, probably because prefixes have fewer word-class restrictions and do not change the word-class of the base (Nevalainen 1999: 335). Thus, native and non-native forms competed to achieve a position in the lexicon. This not only increased the English vocabulary, but also modified the traditional derivational system of the language by the introduction of foreign affixes. As far as we have investigated, the topic has been discussed in Present-Day English and in the history of English. However, the literature is still in need of quantitative and qualitative research in the field of early English medical writing. Therefore, the present paper pursues the following objectives: 1) to analyse the use of the native prefix un- and the non-native dis-, in- and non- in early English medical writing; 2) to assess the distribution of these prefixes across genres; 3) to calculate the morphological productivity of the negative prefixes under study; and 4) to evaluate the contribution of qualitative factors, i.e. the origin of the bases, the different word-classes, and the competion among the different negative prefixes. The data come from the Corpus of Early English Medical Writing.
Keywords: Inglés moderno; Escritos médicos - Redacción; Negative prefixes; Medical writing; Vernacularization; Early modern english